Implementasi Basel I terhadap Tata Kelola Permodalan dan Risiko Kredit Perbankan di Indonesia - Ghozali Maski (Jurusan Manajemen Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2012)
The capital was important to the banks as a buffer against possible losses. For this reason, in 1988 the Bank for International Settlements (BIS) issued a draft capital framework known as the 1988 Basel Accord (Basel I). The purpose of this investigation is to find out the impact of Basel I implementation on capital and credit risk of Indonesian banking over the 2000–2004 period. Based on previous studies, the impact of Basel I was performed by banking behaviour on target capital and target credit risk which is represented by two variable categories, they are bank-specific variable and macroeconomic variable. Bank-specific variables consist of the size of bank, a measure of its asset quality, a measure of its liquidity, and a measure of its profitability whether the macroeconomic condition is represented by the growth of GDP. This research uses a simultaneous equation to analyze adjustments in capital and credit risk. The result estimation of simultaneous equation, were provides evidence, that Basel I has no impact on banking capital and credit risk for well-capitalized banks. This implies that Basel I implementation can not influence banks to change their capital either to improve their credit risk portfolio.Keywords: Basel I, Capital, Credit Risk, and Portofolio.